The sociology of an allocative structure: Housing: In what ways do studies of the housing market in command economies modify our view of ecological processes? - Giaoutzis-Flytzanis, Maria (The Greek Review of Social Research, 1978)
[Δε διατίθεται περίληψη / no abstract available]